The Effect of Capital Gain Tax on Capital Formation, Financial Development and Economic Growth, “Case Study of Selected Europe Union Countries” - Majid Sameti (Journal of Global Pharma Technology, 2018)
The effect of tax on economic activities is an important issue in public finance. The fact that the existing system may decrease the investment motivation and consequently decrease the future life style is a great crisis. In addition to, the effects of tax system on capital formation, it can affect financial development and economic growth. In this paper, by simultaneous equations system in GMM method, the impact of capital gain tax on the capital formation and financial development in selected Europe Union countries (Austria, Belgium, Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Irelands, Italy, Netherlands, Spain and Sweden), will be studied in panel form. The results indicate that the capital gain tax growth rate, with one lag, increases the physical capital formation growth rate. Also, capital gain tax growth rate, with one lag, decreases the financial development growth and increases the economic growth rate. Keywords: Capital gain tax, Capital formation, Economic growth, Simultaneous equations system, GMM.